UPAYA PEMBERDAYAAN USAHA UMKM SEBAGAI SOLUSI PENGENTASAN KEMISKINAN: PRAKTEK PADA CU MITRA PARAHITA, CU TYAS MANUNGGAL DAN CU KRIDHA RAHARDJA - Titus Odong Kusumajati; Stephanus Eri Kusuma; Januari Ayu Fridayani; Maria Angela Diva; Fransisca Desiana Pranatasari (LPPM Universitas Wijaya Putra, 2022)
The purpose of this community service program is to increase the productivity of small businesses as an effort to alleviate poverty. The service method used is to provide material exposure, discussion, practice using working papers and group discussions. The results of the service stated that 88% of participants were very satisfied and satisfied with this training and formulated five follow-up plans, namely (1) Building a business network between fellow CU members (2) Conducting market development activities for member products (3) Identifying and managing potential members so that they will idea development, creativity and collaboration will emerge, (4) Provision of information supporting business development and (5) Business planning and financial budgeting assistance.